INVENTORY MANAGEMENT SYSTEM DESIGN ON ANGEL COLLECTION - Benny Sugiarto; Hery Haryanto (Universitas Internasional Batam, 2022)
This study aims to analyze the inventory management strategy implemented by Angel Collection SMEs in 2021 using the EOQ and ROP methods. The results of data analysis are used to determine the optimal number of orders with the aim of minimizing storage costs consisting of ordering costs and storage costs. The results showed that in September 2020 there were 13 product reorders, in January 2021 as many as 17 products, in June as many as 14 products which is not too much compared to January, and in December as many as 41 products which is the highest number of orders. for 12 months. In the eoq report listed, December 2021 is the most frequent month in which shop owners place orders for reorders due to high demand with a total of 41 products that will be reordered.